Performance Evaluation Study of Stripper in CO2 Removal Unit - Andika Anugrah; Muslikhin Hidayat; Wahyudi Budi Sediawan (Dept. of Chemical Engineering, Diponegoro University, 2023)
An ammonia plant has a very important role in the fertilizer industry. This plant processes natural gas, steam, and air as raw materials into ammonia and carbon dioxide (CO2) products. The ammonia and CO2 products will become feed for the urea plant. One of the units in the ammonia plant is CO2 removal. The CO2 removal unit functions to separate CO2 gas from syngas to be processed to the urea plant, so the performance of the CO2 removal unit is very crucial for the plant. One of the pieces of equipment that supports the performance of the CO2 removal unit is a stripper. This study aims to evaluate the performance of the stripper by arranging a mathematical model and solution for steady-state conditions. One of the stripping performance parameters is CO2 lean loading. Completing mathematical equations using the Matlab program and obtaining profiles of the mole flow rate and temperature along the bed packing stripper. Variables that affect stripper performance include temperature and pH. When compared with operational plant data, the simulation results show an error of below five percent. The optimum operating conditions for the stripping process so that CO2 lean loading is minimum:a. Bottom stripper temperature = 1200C – 1230C,b. pH inlet stripper = 7.9-8.1.